2012
DOI: 10.1016/j.jbiomech.2011.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Regressions for estimating muscle parameters in the thoracic and lumbar trunk for use in musculoskeletal modeling

Abstract: Musculoskeletal modeling requires information on muscle parameters such as cross-sectional area (CSA) and moment arms. A variety of previous studies have reported muscle parameters in the trunk based on in vivo imaging, but there remain gaps in the available data as well as limitations in the generalizability of such data. Specifically, available trunk muscle CSA data is very limited for older adults, lacking entirely in the thoracic region. In addition, previous studies have made measurements in groups of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 31 publications
3
41
1
Order By: Relevance
“…This agrees with the studies of Bogduk et al (1992), Lee et al (2011), McGill et al (1993, Parkkola et al (1992), and Reid and Costigan (1987) and in the range of Cooper et al (1992) and Guzik et al (1996). However, these are smaller than some previous studies (Lee et al, 2006;Wood et al, 1996) and larger than most previous studies (Anderson et al, 2012;Chaffin et al, 1990;Delp et al, 2001;Han et al, 1992;Jorgensen et al, 2003;Kamaz et al, 2007;Kang et al, 2007;Lin et al, 2001;Marras et al, 2001;McGill et al, 1988;Niemelainen et al, 2011;Reid and Costigan, 1985;Seo et al, 2003;Tracy et al, 1989;Tsuang et al, 1993;Tveit et al, 1994). The differences may be due to differences in sampling (sample size, subject characteristics, etc.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This agrees with the studies of Bogduk et al (1992), Lee et al (2011), McGill et al (1993, Parkkola et al (1992), and Reid and Costigan (1987) and in the range of Cooper et al (1992) and Guzik et al (1996). However, these are smaller than some previous studies (Lee et al, 2006;Wood et al, 1996) and larger than most previous studies (Anderson et al, 2012;Chaffin et al, 1990;Delp et al, 2001;Han et al, 1992;Jorgensen et al, 2003;Kamaz et al, 2007;Kang et al, 2007;Lin et al, 2001;Marras et al, 2001;McGill et al, 1988;Niemelainen et al, 2011;Reid and Costigan, 1985;Seo et al, 2003;Tracy et al, 1989;Tsuang et al, 1993;Tveit et al, 1994). The differences may be due to differences in sampling (sample size, subject characteristics, etc.…”
Section: Discussionsupporting
confidence: 89%
“…The angles of the muscle fibers also change with posture (McGill , 2000). Therefore, muscle geometry obtained from supine MRI scans may need to be adjusted for applications in upright postures (Anderson et al, 2012;McGill et al, 1993McGill et al, , 1996. The results of the present study are limited to the supine posture.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to ensure physiologic size and position we used previously collected CT-based measurements of trunk muscle CSA and position performed in a sample of participants from the community-based Framingham Heart Study Offspring and Third Generation Multidetector CT Study [41] to adjust muscle CSA and position in the model. Specifically, we previously measured the CSA and position (medial-lateral (ML) and anterior-posterior (AP) moment arms with respect to the vertebra) of several major trunk muscle groups (rectus abdominis, latissimus dorsi, trapezius, external oblique, internal oblique, erector spinae, mutlifidus, psoas major, quadratus lumborum, serratus anterior, and pectoralis major) in 51 men (mean age ¼ 59.4, Ht ¼ 177.6 cm, Wt ¼ 86.3 kg) [42]. Measurements were made at the mid-plane of each vertebral body between T6 and L5.…”
Section: Model Muscle Anatomymentioning
confidence: 99%
“…A list of these validation studies with the activities they investigated, the characteristics of the study participants, and the primary measurements made is found in Table 3 [45][46][47][48][49][50][51]. For each validation study we created a version of our spine model that was scaled to the average height and weight of the study participants, and we estimated muscle group CSA and AP and ML moment arms from previously published regressions [42] using the average age, sex, height, and weight of the study participants. We then adjusted the CSA and moment arms in the model to match the CSA and moment arms predicted by regression using our muscle adjustment algorithm (Sec.…”
Section: Validation Of Vertebral Compressive Loading Andmentioning
confidence: 99%
“…The present work hence aims to study the effect of variations in BW via a detailed, multi-joint, scalable trunk model (Hajihosseinali et al, 2014) on the L5-S1 disc compression and shear forces during a number of static symmetric tasks. Each activity is simulated using five distinct BWs ranging from 51 to 119 kg while scaling the musculature (moment arms, MA, and physiological cross-sectional areas, PCSA), for the first time, using recent in vivo imaging data (Anderson et al, 2012). Unlike many models that consider BW as a concentrated force on the trunk, in the current model BW is distributed off-centered along the spine with weights of arms and head applied at their mass centers.…”
Section: Introductionmentioning
confidence: 99%